Deteksi Bakteri pada Ibu Hamil dan Post Partum Di Kabupaten Mamuju - Ashriady Ashriady; Abbas Mahmud; Nurdiana Nurdiana (FORIKES, 2020)
Causes of non-obstetric sepsis in pregnant women include malaria, HIV and pneumonia. Urinary tract infections are often linked as the most common cause of infection in pregnancy. Common causes of sepsis are gram-negative bacteria such as Acinetobacter calcoaceticus, Enterobacter aerogenes, Pseudomonas sp and Eschericia coli. High risk for pregnant women is a condition of deviation from normal which directly causes morbidity and death of both mother and baby breech location in premigravida, severe infection/sepsis, preterm labor. Based on this description, researchers were interested in screening bacteria in pregnant women with sepsis in Mamuju Regency in West Sulawesi Province. The purpose of this study was to detect the presence of bacteria in pregnant women in Mamuju Regency. This type of research is descriptive observational research. The time of the study is in the months of May to November 2019. The population was all pregnant women who visit the PKM and/or Hospital in Mamuju Regency, taken using the accidental Sampling method. The results showed a bacterial infection with gram-negative (rod) and gram-positive (round) types in pregnant women. Early detection of the incidence of infection and the cause of the infection is still needed so the researchers recommend that early screening be done on pregnant women. This research can be continued with various specimens such as sputum or wound swabs in women with caesarean section. Keywords: pregnant women; infections; bacteria; gram negative